A Review on Dual-Lens Fluorescence Microscopy for Three-Dimensional Imaging - Li, Xiaoyan; Han, Yubing; Liu, Wenjie; Kuang, Cuifang; Liu, Xu; Hao, Xiang (Frontiers in Physics, 2020)
Three-dimensional (3D) imaging using dual-lens fluorescence microscopies is popular in observing fluorescently labeled biological samples, such as mammalian/model animal cells, tissues, and embryos. Specifically, dual-lens super-resolution fluorescence microscopy methods using two opposing objective lenses allow significantly higher axial resolution and better signal to noise ratio than traditional single-lens counterparts, and thus distinguish more details in 3D images of fine intracellular structures. For 3D imaging of thick tissues and entire embryos, dual-lens light-sheet fluorescence microscopy methods using two objective lenses, either orthogonal or non-orthogonal, to achieve selective plane illumination, can meet the requirements, and thus can be used to observe embryo development and structures of interest in thick tissues. This review summarizes both dual-lens fluorescence microscopy methods, including their principles, configurations, and 3D imaging applications, providing a guideline for biological laboratories with different 3D imaging needs.